In vitro inhibitory potential of methanolic extract of Celosia argentea var. cristata on tyrosinase, acetylcholinesterase and butyrylcholinesterase enzymes - Saqib, Fatima; Janbaz, Khalid Hussain; Sherwani, Maryam Khan (Bangladesh Journal of Pharmacology, 2015)
In the current study, methanol extract of Celosia argentea var. cristata was tested for its inhibitory potential against tyrosinase, acetylcholinesterase and butyrylcholinesterase enzymes at the concentration of 0.5 mM by ELISA microtiter plate assays. A significant tyrosinase inhibitory activity (63.6%), acetylcholinesterase inhibitory activity (80.3%) and butyrylcholinesterse inhibitory activity (68.24%) was shown by crude methanolic extract of C. argentea var. cristata with respective IC50 values of 268.5 ± 0.2 µg/mL, 73.6 ± 0.1 µg/mL and 132.8 ± 0.9 µg/mL. The result of this study reveals the use of C. argentea var. cristata in skin hyperpigmentation, Parkinsons disease and neurodegenerative disorders like Alzheimers disease and dementia.